2006
DOI: 10.1007/s00420-006-0085-8
|View full text |Cite
|
Sign up to set email alerts
|

Biological monitoring of exposure to organophosphate pesticides in children living in peri-urban areas of the Province of Quebec, Canada

Abstract: Mean concentrations of AP were generally higher than those reported in other studies. The observed exposure apparently occurred mainly through the dietary ingestion of OP residues. These data raise questions on the levels of OP residues in Quebec food and the possibility that our participants consumed more fruits and vegetables than those in other studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
3
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 39 publications
0
21
3
4
Order By: Relevance
“…The exposure level in this study was not high compared with children's exposure level in several developed countries such as US, Italy, and Canada [9,10,20]. With similar levels of detection sensitivity, the United States CDC's nationwide survey in 2001 showed that more than 90% of the subjects were positive for at least one of the OP metabolites examined [17].The median levels of dimethyl-and diethyl-DAPs in this study, i.e., 5.8 and 3.1 nmol/L, were approximately 10 times lower than those reported inthe US [10], i.e., 90 and 60 nmol/L, respectively.…”
Section: Discussioncontrasting
confidence: 58%
“…The exposure level in this study was not high compared with children's exposure level in several developed countries such as US, Italy, and Canada [9,10,20]. With similar levels of detection sensitivity, the United States CDC's nationwide survey in 2001 showed that more than 90% of the subjects were positive for at least one of the OP metabolites examined [17].The median levels of dimethyl-and diethyl-DAPs in this study, i.e., 5.8 and 3.1 nmol/L, were approximately 10 times lower than those reported inthe US [10], i.e., 90 and 60 nmol/L, respectively.…”
Section: Discussioncontrasting
confidence: 58%
“…Relatively high %RSD values were shown for the within-run precision at 0.5 g/L (DMTP 25.6% and DETP 27.8%) and between-run precision at 1 g/L (DMP 36.7%, DMTP 51.3% and DETP 23.0%). The urinary DETP concentration of 0.5 g/L is near the geometric mean in the general population [5,12]. On the other hand, geometric means of urinary DMP and DMTP level in the general population are around 10 g/L or more [12,13].…”
Section: Assay Validationmentioning
confidence: 79%
“…Growing concern over the longterm effects of low-level exposure to OPs on human health has encouraged more detailed research both in experimental and in epidemiological settings. Since about 75% of the US Environmental Protection Agency (EPA)-registered OPs are metabolized to dialkyl phosphates (DAPs), including dimethylphosphate (DMP), diethylphosphate (DEP), dimethylthiophosphate (DMTP), diethylthiophosphate (DETP), dimethyldithiophosphate (DMDTP), and diethyldithiophosphate (DEDTP) [2,3], these DAPs in urine have been measured as biomarkers of OP exposure [4,5]. Development of analytical equipment and protocols of sample preparation has made it possible to detect low-level DAPs from various general populations, revealing that OP exposure has commonly occurred even in ordinary daily life.…”
Section: Introductionmentioning
confidence: 99%
“…Samples have also been obtained in larger containers, such as the 500 ml high-density polyethylene wide-mouth containers used in the Farm Family Study (Acquavella et al, 2004) or 1 l polyethylene wide-neck flasks as used in GerES IV from children 5 years and older (or in some girls older than 7 years) (Becker et al, 2008). Plastic collection jugs as well as wide-mouth beakers have also been used (Valcke et al, 2006;Soden et al, 2007).…”
Section: Toilet-trained Childrenmentioning
confidence: 99%
“…This insert is typically used for children who are very young and/or who find it difficult to urinate directly into the specimen cup, for example, girls (Valcke et al, 2006). Some specific brands of commode, ''potty'' or ''hat'' inserts used in previous studies include ''Specipan'' (Baxter Scientific, McGraw Park, IL, USA), lined potty chairs, 750 ml toilet seat inserts and inserts from Sage Products Inc., Crystal Lake, IL, USA (Loewenherz et al, 1997;Curl et al, 2002;Fenske et al, 2002;Shalat et al, 2003, Becker et al, 2008.…”
Section: Toilet-trained Childrenmentioning
confidence: 99%